Defragmentasi Lubang Konstruksi Proses Berpikir Siswa SMP Negeri 6 Dalam Menyelesaikan Soal Literasi Numerasi : DEFRAGMENTASI LUBANG KONSTRUKSI PROSES BERPIKIR SISWA SMP DALAM MENYELESAIKAN SOAL LITERASI NUMERASI - Dewi Nurmalitasari; Miftahul Khoiri (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2024)
Teachers must be aware of and take action regarding students' errors in creating incomplete mathematical concepts, also referred to as construction holes, particularly when it comes to answering numeracy literacy questions. This will help students rebuild their understanding of numeracy literacy questions overall. By using diagrams to depict the answers to numeracy literacy questions both before and after the defragmentation process, this study seeks to identify the places where pupils fall short conceptually. A mixed-methods research methodology was employed for this study, which was conducted in two phases: quantitative analysis was used in the first phase, and qualitative analysis in the second. Based on the research findings, the numeracy component of the statistics curriculum is where the gaps in students' thinking processes are located. Students' thought structures can be strengthened by the use of defragmentation. When answering questions on numeracy and literacy, the defragmentation method utilized is scaffolding at level two, which consists of explaining, reviewing, and restructuring. The mean, mode, and median material in the student results contained construction holes that were later resolved through a scaffolding type that involved three steps: explaining, reviewing, and restructuring. This process helped students avoid making mistakes when answering the questions about the mean, mode, and median.